Faktor Psikologis dan Kualitas Hidup Pasien Penyakit Kronis: Tinjauan Literatur tentang Progresivitas Penyakit dan Dukungan Psikososial - Muhammad Rizki Al Gibran; Dede Riyanto; Indah Laily Hilmi; Hadi Sudarjat (Universitas Muhammadiyah Metro, 2026)
Chronic diseases often require long-term treatment and continuous self-management, yet patients with similar diagnoses may show different clinical outcomes and quality of life. These differences indicate that non-biological factors, particularly psychological conditions, play an important role in disease progression and patient well-being. Psychological risk factors such as stress, depression, and anxiety may worsen chronic disease outcomes, whereas protective factors such as optimism and positive expectations may support adaptive coping and improve quality of life. This literature review aimed to analyze recent scientific evidence on the role of psychological factors in the progression of chronic diseases and the quality of life of patients. A literature review was conducted by examining relevant studies published between 2015 and 2025 and retrieved from Google Scholar and PubMed. The selection process applied predetermined inclusion and exclusion criteria related to chronic disease populations, psychological factors, disease progression, and quality of life outcomes. Fourteen selected articles were analyzed and synthesized narratively. The findings showed that negative psychological factors, particularly stress and depression, were significantly associated with poor glycemic control, increased blood pressure, cardiovascular risk, exacerbation of chronic obstructive pulmonary disease, inflammation-related health problems, and reduced survival among patients with cancer. Anxiety and psychological distress were also related to poorer disease management and lower health-related quality of life. Conversely, protective psychological factors such as optimism and positive expectations were associated with better coping, reduced disability, improved functioning, and longer life expectancy. These findings indicate that psychological factors are important modulators of chronic disease progression through biological, behavioral, and psychosocial mechanisms. This review highlights the need to integrate mental health screening, counseling, psychoeducation, and psychosocial support into chronic disease management. Such integration may help patients regulate stress, strengthen adaptive coping, improve treatment adherence, and enhance overall quality of life.